The Effect of Cyclic Impact Loads on Rock Properties - Ganda Marihot Simangunsong; Yasmine Safitri (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
This study was conducted mainly in the laboratory to evaluate the effect of cyclic impact loads on rock properties. The test sample was a rock-like material made of cement, sand, and water. The sample was given an impact load from a metal pounder that was dropped at various heights. The load was repeatedly applied to the sample until it was damaged and/or until failure. The test results revealed four stages in the fracturing process, starting with cratering of the upper surface of the sample, formation of initial fractures, fracture development along the sample, and finally sample failure. The test results also revealed that with an increase of impact load, the number of cycles until failure decreases. Furthermore, the value of uniaxial compressive strength and Young’s modulus decreases with increasing number of cyclic loads. The decrease is proportional to the increase of the damage value.